PROBLEMS OF REGULATORY AND LEGAL REGULATION OF SAFETY - Evgeny V. Sugak (Russian Studies in Law and Politics)
Safety in any sphere of life is of decisive importance for ensuring the protection of the life and health of citizens, preserving property values, ensuring socio-economic development and is the subject of legal regulation. Regulatory security is an important element of ensuring the stability and sustainability of society and the state. Its goal is to create a safe environment for the life and activities of citizens, protect national security and ensure sustainable development of the country. Legal norms governing security issues in the Russian Federation are enshrined in various branches of law and are regulated by many laws, codes, Presidential decrees, Government resolutions and other government regulations. Some of these documents are fragmentary in nature, deal with private security issues and create local, isolated from each other disparate arrays of legal norms on certain types of security that relate to different branches of law, some partially duplicate each other or even contradict each other. At the same time, in some of the most important areas of security, there are no necessary federal laws and they are regulated by secondary legal acts - presidential decrees and government decrees. The article analyzes the state of regulatory and legal support for security and the preliminary results of reforms in the system of technical regulation and control and supervisory activities (“regulatory guillotine”). Their main shortcomings are identified and options for eliminating them are proposed.